Pengaruh Flexing Di Sosial Media Dalam Perspektif Islam - Salam, Rangga; Sundari, Dewi (Al-Sharf: Jurnal Ekonomi Islam, 2023)
Technological developments now make it easier for people to carry out flexing activities, because now people can get internet access both domestically and abroad in the world of social media. The problem that is very widespread recently is regarding trends or activities on social media which are very popular with today's society, especially teenagers to adults. The activity they do on social media is nothing but the activity of showing off things that are not well shown but are now normal and normal. Flexing behavior uses a lot of open space in social media which results in going too far, which has absolutely no benefit to the public. Flexing activities are only made to the extent of fulfilling content, in which there are no creations or learning values that can be benefited. The purpose of this study is to discuss flexing which is currently rife and starting to ignore Islamic law. With this research, the writer describes and analyzes the meaning of flexing, explains the interpretation of Al-Quran verses about flexing. The method in this research is library research. The source of this research study comes from articles, books, news, and opinions about the phenomenon of flexing in the perspective of Islamic Economics. Islamic economics assesses flexing as one of the excessive behaviors. The result of this study is the trend of flexing, namely the activity of showing off what one has by standing out towards flexing activities on social media which can be accessed easily and spread widely. Islam teaches the importance of behaving in a balance between life in this world and in the hereafter, between physical and spiritual needs, between one's own needs and that of others. Islamic economics offers an offer to prevent flexing behavior, namely: Knowing what is needed, Consuming Halal and Toyyib goods, Spending wealth for the life of the world and the hereafter, Looking simple and not showing off wealth.